Shh! we have a plan - Haughton, Chris (Somerville, Massachusetts : Candlewick Press, 2014)
Spotting an exquisite bird in a tree, three friends execute a series of stealthy plans to capture the bird only to have their efforts foiled, while their quiet, observant companion stretches out his hand to execute a plan of his own.
Keywords: Bird trapping -- Fiction; Hunters -- Fiction; Birds -- Fiction; Trapping -- Fiction; Hunters -- Fiction